2020
DOI: 10.3390/su12031242
|View full text |Cite
|
Sign up to set email alerts
|

Research on Improving Concrete Durability by Biomineralization Technology

Abstract: The interfacial transition zone (ITZ) around aggregates in concrete is a weak area with higher porosity than the matrix; it breaks easily under stress and is not conducive to the durability of concrete. However, the ITZ in concrete is full of calcium hydroxide crystals, which can provide the calcium source required for biomineralization. In view of this, this study aims to use the biological activity (i.e., biomineralization technology) existing in nature to enhance the ITZ in concrete and repair concrete crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Calcite deposition in this gap will make the compressive strength of concrete to be higher. This result is in line with research conducted by Chen et al [34].…”
Section: Compressive Strength Of Concretesupporting
confidence: 93%
“…Calcite deposition in this gap will make the compressive strength of concrete to be higher. This result is in line with research conducted by Chen et al [34].…”
Section: Compressive Strength Of Concretesupporting
confidence: 93%
“…There is a greater tendency for studies with more than two experimental groups and a control group, as well as factorial designs. It can be observed that the most used microorganisms correspond to Bacillus subtilis [10,13,15,21,24] [27,28,30-32,34-37] and Sporosarcina pasteurii [14,23,26,[38][39][40][41][42][43][44]. In the case of Bacillus subtilis, its inherent effect has been tested and its concentration used, the contribution of other conditions such as the type of fiber, recycled material, type of immobilization, substrate used and genetic modification.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, MICP directed by urea hydrolysis, denitrification and dissimilatory sulfate reduction are the mainstay of bioconcrete production, with demonstrated improvements in mechanical strength and durability (Castro‐Alonso et al, 2019 ). Ureolytic biomineralization is used in a broad range of applications in construction and environmental protection, such as self‐healing concrete (Chen et al, 2020 ), bio‐bricks (Randall & Naidoo, 2018 ), dust stabilization (Aletayeb et al, 2021 ), ground improvement (Liu, Fan, et al, 2021 ; Liu, Zhang, et al, 2021 ) and bioremediation (Liu, Zhang, et al, 2021 ). A further benefit of using biomineralization in the production of building materials is that substrates such as granite, brick, marble and binders like fly ash, contain natural radioactivity, although this is typically very, very low but can result in unsafe levels of radon, which is a naturally occurring, hazardous radioactive gas that is formed from the decay of uranium in soil, rock and water (Eštoková & Palaščáková, 2013 ).…”
Section: The Microbiology and Architectural Contextmentioning
confidence: 99%